Simeprevir plus sofosbuvir for eight or 12 weeks in treatment‐naïve and treatment‐experienced hepatitis C virus genotype 4 patients with or without cirrhosis. Issue 2 (27th October 2016) - El Raziky, M.; Gamil, M.; Ashour, M. K.; Sameea, E. A.; Doss, W.; Hamada, Y.; Van Dooren, G.; DeMasi, R.; Keim, S.; Lonjon‐Domanec, I.; Hammad, R.; Hashim, M. S.; et al.
Abstract: The OSIRIS study investigated efficacy and safety of simeprevir plus sofosbuvir for eight or 12 weeks in hepatitis C virus (HCV) genotype 4‐infected patients with METAVIR F0‐F4 fibrosis. Sixty‐three patients (33 treatment‐naïve and 30 peg‐interferon/ribavirin (Peg‐IFN/RBV)‐experienced) enrolled in a partly randomized, open‐label, multicentre, phase IIa study. Patients with F0‐F3 fibrosis were randomized (1:1) into two groups (A1 and A2), stratified according to treatment experience and METAVIR score, to receive either eight weeks (Group A1, n=20) or 12 weeks (Group A2, n=20) of treatment. Patients with compensated cirrhosis (METAVIR F4) received 12 weeks of treatment (Group B, n=23). Treatment comprised simeprevir 150 mg and sofosbuvir 400 mg daily. The primary efficacy endpoint was sustained virologic response 12 weeks after planned end of treatment (SVR12). Safety and tolerability were assessed throughout. Overall, 92% (95% CI: 82‐97) of patients achieved SVR12; 75% (15/20) in Group A1 and 100% in groups A2 and B. Patients who did not achieve SVR12 (n=5) experienced viral relapse during the first 32 days following treatment and were all prior Peg‐IFN/RBV null responders. The most commonly reported treatment‐emergent adverse events (TEAEs) were asymptomatic lipase increase (14%), pruritus (14%), headache (13%) and hyperbilirubinaemia (11%). No patients discontinued due to TEAEs. In conclusion, simeprevir plus sofosbuvir for 12 weeks achieved a 100% SVR rate in HCV genotype 4‐infected patients with or without compensated cirrhosis (ClinicalTrials.gov: NCT02278419). The AE and laboratory profile were favourable and consistent with previous data for simeprevir plus sofosbuvir in eight‐ and 12‐week regimens.